Strength training and detraining in female dancesport athletes: adaptations and retention of lower limb muscle architecture, strength, and dance performance - Lu, J.; Lei, T.-H.; Zamri, E. N. B.; Shaharudin, S. (BMC Sports Science, Medicine and Rehabilitation, 2026)
Background Although strength training enhances performance in dancers, limited evidence exists regarding its effects on lower limb muscle architecture and the persistence of these adaptations following detraining. Therefore, this study examined the effects of a 12-week structured strength training program followed by 8 weeks of detraining on muscle architecture, isokinetic strength, and dance performance in female dancesport athletes.